LncRNA PVT1 promotes cervical cancer progression by sponging miR-503 to upregulate ARL2 expression - Liu, Weiwei (Open Life Sci, 2021)
Cervical cancer (CC) is a huge threat to the health of women worldwide. Long non-coding RNA plasmacytoma variant translocation 1 gene (PVT1) was proved to be associated with the development of diverse human cancers, including CC. Nevertheless, the exact mechanism of PVT1 in CC progression remains unclear. Levels of PVT1, microRNA-503 (miR-503), and ADP ribosylation factor-like protein 2 (ARL2) were measured by quantitative reverse transcription-polymerase chain reaction or western blot assay. 3-(4,5)-Dimethylthiazole-2-y1)-2,5-biphenyl tetrazolium bromide (MTT) and flow cytometry were used to examine cell viability and apoptosis, respectively. For migration and invasion detection, transwell assay was performed. The interaction between miR-503 and PVT1 or ARL2 was shown by dual luciferase reporter assay. A nude mouse model was constructed to clarify the role of PVT1 in vivo. PVT1 and ARL2 expressions were increased, whereas miR-503 expression was decreased in CC tissues and cells. PVT1 was a sponge of miR-503, and miR-503 targeted ARL2. PVT1 knockdown suppressed proliferation, migration, and invasion of CC cells, which could be largely reverted by miR-503 inhibitor. In addition, upregulated ARL2 could attenuate si-PVT1-mediated anti-proliferation and anti-metastasis effects on CC cells. Silenced PVT1 also inhibited CC tumor growth in vivo. PVT1 knockdown exerted tumor suppressor role in CC progression via the miR-503/ARL2 axis, at least in part.